2010
DOI: 10.1097/aog.0b013e3181c52132
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Compared With Glyburide in Gestational Diabetes

Abstract: I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
140
1
11

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 154 publications
(160 citation statements)
references
References 11 publications
8
140
1
11
Order By: Relevance
“…They found failure rate of metformin (34.7%) 2.1 times higher than glyburide (16.2%). 17 Failure rate of glyburide in this study (16.2%) is significantly higher than the 4% failure rate reported in the initial study by Langer et al, failure rate of metformin in this study (34.7%) is in line with the study reported by Rowan et al in which 46.3% of patientsreceiving metformin received supplemental insulin to achieve euglycemia. 19,20 Among maternal variables glycemic control of both groups were comparable.…”
supporting
confidence: 71%
See 2 more Smart Citations
“…They found failure rate of metformin (34.7%) 2.1 times higher than glyburide (16.2%). 17 Failure rate of glyburide in this study (16.2%) is significantly higher than the 4% failure rate reported in the initial study by Langer et al, failure rate of metformin in this study (34.7%) is in line with the study reported by Rowan et al in which 46.3% of patientsreceiving metformin received supplemental insulin to achieve euglycemia. 19,20 Among maternal variables glycemic control of both groups were comparable.…”
supporting
confidence: 71%
“…Studies were performed in the Mexico and Brazil, and diagnostic criteria were those of Carpenter and Coustan and the WHO respectively. 17,18 We undertook this study in order to determine the effects of glyburide and metformin in the Indian pregnant womendiagnosed to have gestational diabetes mellitus according to DIPSI criteria and to compare each other.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, although the success rate in a pioneer study was 96% for patients not requiring insulin (1), later studies have not demonstrated the same efficacy, with 20-25% and 45% of the patients taking glyburide and metformin, respectively, requiring second-line therapy with insulin because of poor glycemic control or adverse effects (2,9). Second, studies comparing the efficacy and safety of glyburide versus metformin have conflicting results regarding the best medication to use as a first-line therapy (10)(11)(12). Finally, in studies evaluating oral hypoglycemic medications for GDM, in case of a treatment failure, the second-line treatment was always insulin (1)(2)(3)(8)(9)(10)(11)(12)(13)(14).…”
mentioning
confidence: 99%
“…Second, studies comparing the efficacy and safety of glyburide versus metformin have conflicting results regarding the best medication to use as a first-line therapy (10)(11)(12). Finally, in studies evaluating oral hypoglycemic medications for GDM, in case of a treatment failure, the second-line treatment was always insulin (1)(2)(3)(8)(9)(10)(11)(12)(13)(14).…”
mentioning
confidence: 99%